PENGARUH BERKUMUR LARUTAN SELEDRI TERHADAP PENURUNAN PLAK SKOR PADA SISWA KELAS V DI SDN LANDASAN ULIN BARAT 1 - Annisa Oktavia; Siti Sabátul habibah; Isnawati Isnawati (JURNAL TERAPIS GIGI DAN MULUT, 2021)
Data from the Republic of Indonesia Ministry of Health 2013 shows that the percentage of people with dental and mouth problems in South Kalimantan is 36.1%. Plaque is one of the causes of caries that occurs in the world population in the amount of 75-90%. Gig plaque is a soft layer that is firmly attached to the surface of a tooth which if not cleaned will cause periodental disease and caries due to poor oral hygiene. This study aims to determine the effect of rinsing celery solution on plaque score reduction in fith grade students at SDN Landasan Ulin Barat 1. This type of research is a type of library research, the research design is an experimental study and is laboratory in nature. The results to this study showed that the ethanol extract of celery stems with concentrations of 12.5%, 15%, 25%, 50%, 75% and 100% had smaller inhibitory zones than the positive control group. The inhibition zone diameter of the K + group is 6 mm, then K 12.5% ​​is 1 mm, K 15% is 1 mm, K 25% is 1 mm, K 50% is 1.3 mm, K 75% is 1.6 mm and 100% K by 1.6 mm and the negative control group has no inhibition zone. The conclusion of this study is that the ethanol extract of celery stems has an antibacterial power against the growth of Streptococcus mutans ATCC 35668 with inhibitory power under chlorhexidine. The best concentration (the biggest inhibition zone) is concentration with 75% extract.